Analysis of the implementation of property sales administration at PT Satwika Permai Indah Jakarta - Peter Rajagukguk; Arief Fadholi (Privietlab, 2021)
Administration is an important activity in managing a business. The role of administration is very influential in supporting business growth, without good administrative handling, business actors will have difficulty knowing the data that the company wants. The purpose of this study was to determine the implementation of property sales administration at PT Satwika Permai Indah Jakarta, and various obstacles and solutions to overcome them. Qualitative descriptive research form with data collection through observation, interviews, and documentation. The results showed that PT Satwika Permai Indah Jakarta in the implementation of cash and credit sales administration, there were 10 parties involved, namely consumers, sales marketing and admins, cashiers, finance, taxes, law, the Home Ownership Credit (HOC) team, banks, directors, as well as a notary. Documents required include Proof of Marketing Receipt, PPJB, SP3K, AJB, SSP, Certificate of Ownership, Certificate. The process starts from the consumer selecting the unit, making the payment, interviewing the bank's credit analyst, until it is ratified by a notary, and PT Satwika Permai Indah handing over the unit that is ready to be occupied by the consumer. In making land deeds, sometimes there are delays due to incomplete or invalid consumer data. This is a concern for legal parties to remind consumers to update the necessary data.